The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1039/b807821a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HEPA vacuum cleaning and dry steam cleaning in reducing levels of polycyclic aromatic hydrocarbons and house dust mite allergens in carpets

Abstract: Dry steam cleaning, which has gained recent attention as an effective method to reduce house dust mite (HDM) allergen concentration and loading in carpets, was evaluated in this study for its efficacy in lowering levels of polycyclic aromatic hydrocarbons (PAHs) as well as HDM allergens. Fifty urban homes with wail-to-wall carpets, mostly low-income and with known lead contamination, were studied in 2003 and 2004. Two carpet-cleaning interventions were compared: Repeated HEPA (High Efficiency Particulate Air f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
2
14
0
1
Order By: Relevance
“…Studies examining the effect of vacuuming in reducing dust mite concentrations have yielded mixed results; however, the consensus is that vacuuming does decrease the bulk of dust mite allergen in carpet [13,14]. The effi ciency of dust mite allergen extraction from carpets by vacuuming is largely infl uenced by pile height and the overall condition of the carpet.…”
Section: Exposure Mitigationmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies examining the effect of vacuuming in reducing dust mite concentrations have yielded mixed results; however, the consensus is that vacuuming does decrease the bulk of dust mite allergen in carpet [13,14]. The effi ciency of dust mite allergen extraction from carpets by vacuuming is largely infl uenced by pile height and the overall condition of the carpet.…”
Section: Exposure Mitigationmentioning
confidence: 94%
“…However, some evidence suggests that dry steam cleaning, when added to an intensive vacuuming regimen, provides some added reduction in dust mite allergen compared with vacuuming alone. In 2009, Yu et al [14] found that an additional 5% reduction in dust mite allergen was achieved when dry steam cleaning was added to a regular vacuuming regimen. A similar study reported that lower levels of dust mite allergen were sustained for a greater duration when a dry steam cleaning treatment was added to a rigorous vacuuming schedule [16].…”
Section: Exposure Mitigationmentioning
confidence: 98%
“…Statistics after cleaning (mg/cm 2 ) were a minimum of 0.0019, a maximum of 0.289, a median of 0.0102, an arithmetic mean of 0.0463, an arithmetic standard deviation of 0.0863, a geometric mean of 0.0146 (mean, standard deviation, and geometric mean were calculated from the raw data provided by Roberts et al 1999). Yu et al (2009) collected 50 dust samples from carpets in New Jersey homes before and after cleaning. The houses were identified as mostly low-income, urban residences.…”
Section: Dust Surface Loading (Dsl): Hard Surfacesmentioning
confidence: 99%
“…(69) A steam vapor machine differs from the commonly known "steam cleaner" which is a hot-water carpet shampooing machine. Steam was demonstrated to be effective in reducing dust mite populations.…”
Section: Figure 2 Percent Biocontaminants Reduction By Treatment Typementioning
confidence: 99%